Partisipasi Orang Tua Dalam Memotivasi Belajar Anak - Nurdin, Said; Rosita, Dara; Eliana, Eliana (Universitas Pendidikan Muhammadiyah Sorong, 2022)
Learning motivation is an important factor that must be owned by every student so that learning activities can run well and to optimize children's learning motivation it is necessary to have participation shown by parents. The purpose of this study was to describe the participation of parents in motivating children's learning at one of the first high schools or Madrasah Tsanawiyah in Aceh Besar. This research approach is quantitative with descriptive method. The population of this study was all students of one of the first high schools or Madrasah Tsanawiyah in Aceh Besar with a sample of 100 students consisting of grades VII, VIII and XI. Random sampling technique was used as a sampling method. The data collection technique used a non-test instrument in the form of a parental participation scale in motivating children's learning which was designed by the researcher based on the operational definition of the variable. The results of the study illustrate that parental participation in motivating children to learn is in the medium category with a percentage of 81%. This means that parents have participated, but only some parents have motivated their children to learn.